Nanobubble Mediated Gene Delivery in Conjunction With a Hand-Held Ultrasound Scanner - Kida, Hiroshi; Nishimura, Koyo; Ogawa, Koki; Watanabe, Akiko; Feril, Loreto B.; Irie, Yutaka; Endo, Hitomi; Kawakami, Shigeru; Tachibana, Katsuro (Frontiers in Pharmacology, 2020)
Recent research has revealed that nanobubbles (NBs) can be an effective tool for gene transfection in conjunction with therapeutic ultrasound (US). However, an approach to apply commercially available hand-held diagnostic US scanners for this purpose has not been evaluated as of now. In the present study, we first compared in vitro, the efficiency of gene transfer (pCMV-Luciferase) with lipid-based and albumin-based NBs irradiated by therapeutic US (1MHz, 5.0 W/cm2) in oral squamous carcinoma cell line HSC-2. Secondly, we similarly examined if gene transfer in mice is possible using a clinical hand-held US scanner (2.3MHz, MI 1.0). Results showed that lipid-based NBs induced more gene transfection compared to albumin-based NBs, in vitro. Furthermore, significant gene transfer was also obtained in mice liver with lipid-based NBs. Sub-micro sized bubbles proved to be a powerful gene transfer reagent in combination with conventional hand-held ultrasonic diagnostic device.